EQUITY OF PROFILES BETWEEN COMPUTER-BASED AND CLASSICAL MODALITY OF MMPI-202 - Janičić, Bojan (Primenjena psihologija, 2015)
With the increasing application of computer-based tests, a problem of equivalence between computerized and classical forms has appeared. Studies regarding equivalence of computerbased and paper and pencil forms of psychological tests usually examined the impact of individual differences and variables such as computer experience and computer anxiety. Previous research gave mixed results. The aim of this study was to determine whether there were differences in the profiles of subjects on computer-based and classical modality of the MMPI-202. In addition, the aim of this study was to examine the influence of gender, age, education level, computer experience, and computer anxiety on examinees’ profiles on the computer and the classical modality of this test. There were no significant differences in examinees’ profiles which could be attributed to the modality of testing.